Multiplying worlds romanticism, modernity, and the emergence of virtual reality - Otto, Peter, 1953- (Oxford : Oxford University Press, 2011)
This title argues that modern forms of virtual reality first appear in the urban/commercial milieu of London in the late 18th and early 19th century. To establish this aetiology it maps the emergence of virtual realities in popular entertainment Enlightenment schemes for managing the real, and Romantic literature and art.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Romanticism -- Great Britain; English literature -- 18th century -- History and criticism; English literature -- 19th century -- History and criticism; Virtual reality in literature; Amusements -- Great Britain -- History -- 18th century